A longitudinal study of facial growth of Southern Chinese in Hong Kong: Comprehensive photogrammetric analyses - Wen, Yi Feng (PLoS One, 2017)
INTRODUCTION: Existing studies on facial growth were mostly cross-sectional in nature and only a limited number of facial measurements were investigated. The purposes of this study were to longitudinally investigate facial growth of Chinese in Hong Kong from 12 through 15 to 18 years of age and to compare the magnitude of growth changes between genders. METHODS AND FINDINGS: Standardized frontal and lateral facial photographs were taken from 266 (149 females and 117 males) and 265 (145 females and 120 males) participants, respectively, at all three age levels. Linear and angular measurements, profile inclinations, and proportion indices were recorded. Statistical analyses were performed to investigate growth changes of facial features. Comparisons were made between genders in terms of the magnitude of growth changes from ages 12 to 15, 15 to 18, and 12 to 18 years. For the overall face, all linear measurements increased significantly (p < 0.05) except for height of the lower profile in females (p = 0.069) and width of the face in males (p = 0.648). In both genders, the increase in height of eye fissure was around 10% (p < 0.001). There was significant decrease in nasofrontal angle (p < 0.001) and increase in nasofacial angle (p < 0.001) in both genders and these changes were larger in males. Vermilion-total upper lip height index remained stable in females (p = 0.770) but increased in males (p = 0.020). Nasofrontal angle (effect size: 0.55) and lower vermilion contour index (effect size: 0.59) demonstrated large magnitude of gender difference in the amount of growth changes from 12 to 18 years. CONCLUSIONS: Growth changes of facial features and gender differences in the magnitude of facial growth were determined. The findings may benefit different clinical specialties and other nonclinical fields where facial growth are of interest.